Being Christians in Muslim-majority Malaysia : The Kelabit and Lun Bawang Experiences in Sarawak - Poline, Bala (ISEAS–Yusof Ishak Institute, 2014)
INTRODUCTION: RELIGIOUS MINORITIES CHALLENGES IN MALAYSIA